α-Lithiated α-Heterosubstituted 2-Alkyloxazolines: Key Players in Organic Synthesis - Florio, Saverio (Synlett, 2013)
The chemistry and synthetic utility of α-lithiated haloalkyloxazolines, oxazolinyl epoxides, and aziridines are highlighted in this account. These lithiated species, which are easily generated, can be captured by electrophiles to give more functionalized derivatives. Spectroscopic and computational studies have proved useful, not only in relation to understanding the chemistry of lithiated species in general, but also in the elucidation of the mechanisms of their lithiation and the stereochemistry of their reactions. The combination of bench experiments with spectroscopic investigations and density functional theory calculations has contributed enormously to increasing the synthetic potential of the lithiated oxazolines that are described in this account.1 Introduction2 Lithiation and Reactions of 2-(Haloalkyl)oxazolines and Their Applications2.1 Synthesis of Oxazolinyl and Formyl Epoxides2.2 Synthesis of Oxazolinylcyclopropanes2.3 Synthesis of Oxazolinyl Estrones2.4 Synthesis of Alkenyl Oxazolines and Oxazolinyl Oxazetidines2.5 Synthesis of Oxazolinyl Aziridines2.6 Vicarious Nucleophilic Substitution Reactions of (Chloroalkyl)oxazolines: Synthesis of (Nitrobenzyl)oxazolines and Dinitrophenyl(dioxazolinyl)ethenes3 Lithiated Oxazolinyloxiranes: Generation and Reactions3.1 Generation and Reactions of α-Lithiated Oxazolinyloxiranes3.2 Synthesis of Oxazolinylaryl Alkanones3.3 Synthesis of Allylic Alcohols from Oxazolinyloxiranes3.4 Isomerization of Oxazolinyl Allylic Alcohols: Synthesis of 3-Alkylidene-2-iminooxetanes3.5 Reactions of Lithiated Oxazolinyloxiranes with Nitrones: Synthesis of α-Epoxy γ-Amino Acids3.6 Reactions of Lithiated Oxazolinyloxiranes with α,β-Unsaturated Fischer Carbene Complexes: Synthesis of Cyclopropyl-Fused γ-Butyrolactones3.7 On the Stereochemistry of α-Lithiated Oxazolinyloxiranes3.8 Synthesis of Optically Active ortho-Sulfinylphenyl Oxazolinyl Epoxy Alcohols3.9 α-Lithiated Benzothiazolyloxiranes3.10 α-Lithiated Benzotriazolyloxiranes3.11 Synthesis of α,β–Epoxy-γ-butyrolactones from β-Lithiated Oxazolinyloxiranes3.12 Synthesis of α,β-Epoxy-γ-amino acids and α,β-Epoxy-γ-butyrolactams3.13 Synthesis of Polysubstituted Oxazolinyl Cyclopropanes3.14 Lithiation Of Terminal Oxazolinyloxirane: Synthesis of Trisubstituted Oxazolinyloxiranes and an (E)-1,4-Dioxazolinyl-1,4-diphenylbut-2-ene-1,4-diol4 Lithiated Oxazolinyl Aziridines4.1 α-Lithiated N-Alkyl(aryl)oxazolinylaziridines: Synthesis of Aziridinolactones4.2 Lithiation of N-Alkyl Terminal Aziridines4.3 Lithiation of Heterosubstituted Oxazolinylaziridines4.4 Lithiation of N-Sulfonyl- and N-Phosphinylaziridines5 Concluding Remarks
Keywords: epoxides; asymmetric synthesis; heterocycles; lithiation; lactones; lactams